FENOLOGIA DE HYDROCOTYLE LEUCOCEPHALA CHAM. - Borgignon, Ozair José; Piccolo, Antonia Lélia Guadagnuci [UNESP] (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 1981)
Hydrocotyle leucocephala Cham. is a shade-species growing in the Horto Florestal “Navarro de Andrade”, Rio Claro, São Paulo. This place is located in an area with a mean annual rainfall of 1446,5 mm and a temperature of 19,6 ºC. The phenophases studied, leaf flushing, flowering and fruiting exhibits a high peak in the wet season (October-April) and the leaf fall in the dry and cold season (April-September).

Hydrocotyle leucocephala Cham. é uma espécie de sombra que cresce no Horto Florestal “Navarro de Andrade”, Rio Claro, São Paulo. Nesta área a precipitação média anual é de 1446,5 mm e a temperatura 19,6ºC. As fenofases de brotação, floração e frutificação ocorrem na estação úmida (Outubro-Abril) e a queda de folhas na estação seca (Abril-Setembro).